211k views
0 votes
Mary said that -7 + 4g was equivalent to the original expression -4g + 7. Is she correct ? Explain Enter Answor Here

1 Answer

1 vote

Given:

Original expression ==> -4g + 7

Mary said that the expression -7 + 4g is equivalent to the original expression.

To verify Mary's claim, let's rearrange the expression using asscociative property of addition.

We have:

-7 + 4g ==> 4g - 7

After rearranging the expression -7 + 4g, we have 4g - 7.

Thus, we now have the two expressions:

Original expression ==> -4g + 7

Mary's expression ==> 4g - 7

We can see that both expressions are different. Therefore, Mary is not correct.

ANSWER:

No, Mary's claim is n

User Sameera Jayasoma
by
5.1k points